Dynamic responses of laminated beams under a moving load in thermal environment - Akbaş, Şeref Doğuşcan (Techno-Press, 2020)
The goal of this study is to investigate dynamic responses of laminated composite beams under a moving load with thermal effects. The governing equations of problem are derived by using the Lagrange procedure. The transverse -shear strain and rotary inertia are considered within the Timoshenko beam theory. The material properties of laminas are considered as the temperature dependent physical property. The differential equations of the problem are solved by the Ritz method. The solution step of dynamic problem, the Newmark average acceleration method is used in the time history. A compassion study is performed for accuracy of used formulations and method. In the numerical results, the effects of velocity of moving load, temperature values, the fiber orientation angles and the stacking sequence of laminas on the dynamic responses of the composite laminated beam are investigated.
Akbas, Seref Doguscan/0000-0001-5327-3406
Keywords: laminated composites; moving load problems; temperature effect; ritz method